Analisis SWOT Efektivitas Beton Cast In Situ Pada Saluran Irigasi Jogging Track Desa Wisata Baha, Kecamatan Mengwi - Ni Ketut, Suparmi; Anak Agung, Sagung Putri Gita Suari Samitra; I Gede, Restu Prasetyac (Universitas Pendidikan Nasional, 2024)
Baha Tourism Village is one of the tourist destinations in Badung Regency, featuring a 6-kilometer jogging track. This study aims to determine the effectiveness of using cast-in-situ concrete in rehabilitating the irrigation canal adjacent to the jogging track. A SWOT matrix analysis was employed. Based on the analysis, four sets of alternative strategies can be implemented for the rehabilitation of the Subak Lepud irrigation canal in Baha Tourism Village compared to precast U-ditch concrete. The SO (Strength-Opportunity) strategy reveals that the factor to be maintained to seize opportunities is the use of cast-in-situ concrete, which is more economical due to its long lifespan. Furthermore, the WO (Weakness-Opportunity) strategy involves using a time schedule where all construction plans, from formwork installation to concrete pouring, are incorporated to maximize time, cost, and quality. The ST (Strength-Threat) strategy indicates that there are numerous stakeholders involved in the canal project, while the WT (Weakness-Threat) strategy suggests that to minimize the failure of cast-in-situ concrete mixtures, supervision of materials, concrete mix quality, and occupational health and safety (OHS) must be optimized.